Effect of Y2O3–CeO2 two-phase dispersion strengthening on the grain size and tensile properties of Mo alloys - DUAN Lin-lin; FENG Peng-fa; DANG Xiao-ming (Fenmo yejin jishu)
Mo–Y–Ce alloys doped by yttrium oxide (Y2O3) and cerium oxide (CeO2) in different mass fraction were prepared by the nanometer spray doping technology and the powder metallurgy method. The two-phase dispersion strengthening effect of Y2O3 and CeO2 on the grain size and mechanical properties of Mo alloys at room temperature was studied. The results show that Y2O3 restrains the abnormal growth of the individual grains and has the effect of precipitation strengthening. The mechanical properties of the Mo–Y alloy wires are closely related to the doping amount of Y2O3. When the mass fraction of Y2O3 is 0.60%, the tensile strength and yield strength of the ϕ1.8-mm Mo–Y alloy wires reach 1050 and 923 MPa, respectively. Because of the semi-coherent relationship between CeO2 and the Mo matrix, CeO2 has the good toughening effect. When the mass fraction of CeO2 is 0.06%~0.08%, the grain size of the sintered Mo–Y–Ce alloys is smaller than 10 μm, the tensile strength and yield strength of the ϕ1.8-mm Mo–Y–Ce alloy wires are 1130 and 1018 MPa, respectively, the elongation reaches 28.5%. The tensile strength of ϕ0.18-mm Mo–Y–Ce alloy wires reaches 2510 MPa. The optimal composition of the Mo–Y–Ce two-phase dispersion strengthening Mo alloys is Mo–0.6Y2O3–(0.06~0.08)CeO2.